Mechanochemical Encapsulation of Fullerenes in Peptidic Containers Prepared by Dynamic Chiral Self‐Sorting and Self‐Assembly. Issue 9 (25th January 2016) - Szymański, Marek; Wierzbicki, Michał; Gilski, Mirosław; Jędrzejewska, Hanna; Sztylko, Marcin; Cmoch, Piotr; Shkurenko, Aleksander; Jaskólski, Mariusz; Szumna, Agnieszka
Abstract: Molecular capsules composed of amino acid or peptide derivatives connected to resorcin[4]arene scaffolds through acylhydrazone linkers have been synthesized using dynamic covalent chemistry (DCC) and hydrogen‐bond‐based self‐assembly. The dynamic character of the linkers and the preference of the peptides towards self‐assembly into β‐barrel‐type motifs lead to the spontaneous amplification of formation of homochiral capsules from mixtures of different substrates. The capsules have cavities of around 800 Å 3 and exhibit good kinetic stability. Although they retain their dynamic character, which allows processes such as chiral self‐sorting and chiral self‐assembly to operate with high fidelity, guest complexation is hindered in solution. However, the quantitative complexation of even very large guests, such as fullerene C60 or C70, is possible through the utilization of reversible covalent bonds or the application of mechanochemical methods. The NMR spectra show the influence of the chiral environment on the symmetry of the fullerene molecules, which results in the differentiation of diastereotopic carbon atoms for C70, and the X‐ray structures provide unique information on the modes of peptide–fullerene interactions. Abstract : Molecular capsules : Peptidic capsules based on minimal β‐barrel motifs have been formed from short peptides and a dynamic covalent chemistry approach. The complexation of fullerenes (see figure), used as surface‐inactive probes, was achieved by chemical and mechanochemical methods.